Waste not, want not : eliminating Patagonia's pre- and post-consumer textile waste - Dzombak, Rachel; Rosen, Christine, active 2020; Pendleton-Knoll, Seren; O'Neill, Kate; Chesbrough, Henry William; Strand, Robert, active 2020; Critcher, Clayton (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2020)
Patagonia has set a goal of eliminating all textile waste by 2025. As a leader in the sustainable apparel industry, this includes not only the cut-and-sew scraps and the liability fabrics, but also the end of life for all of its garments. In order to achieve this goal, innovation must occur throughout the entire lifecycle of Patagonia's products: from the design and the manufacturing, to the consumer behavior side. The company has sought to change the way customers think about clothing - encouraging them to buy fewer, more durable products based on real needs. Patagonia has also worked to create alternatives to landfill for garments at the end-of-life - like repair, recycling, and upcycling. With the mission of: "We are in business to save our home planet," Patagonia must achieve this in such a way that other companies can replicate. The case explores aspects of this goal through the eyes of a number of Patagonia employees who work on different teams within the apparel and gear business.
Originally Published InDzombak, R., Rosen, C., Pendleton-Knoll, S., O'Neill, K., Chesbrough, H., Strand, R. & Critcher, C. (2020). Waste not, want not: Eliminating Patagonia's Pre- and Post-Consumer Textile Waste. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Patagonia, Inc. -- Case studies; Clothing trade -- Sustainable methods -- Case studies